PENGGUNAAN MODEL MURDER DENGAN MEDIA GAMBAR DALAM PENINGKATAN PEMBELAJARAN IPA PADA SISWA KELAS IV SDN 1 SELANG TAHUN AJARAN 2014/2015 - Permatahati, Diyan Riski (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application of MURDER Model Using Image Media in Improving Natural Science Learning at The Fourth Grade Students of SDN 1 Selang in the Academic Year of 2014/2015. The objectives of this study are: learning improvement of natural science learning by implementing MURDER model using image media, describe the steps of application MURDER model using image media, and to describe problems and solutions in the application of MURDER model using image media. This research is collaborative Classroom Action Research (CAR) conducted in three cycles, consisting of planning, implementation, observation, and reflection on each cycle. The subject of this research was 23 students. The conclusion of this research is the application of MURDER model using image media can improve natural science learning outcomes for the fourth grade students of SDN 1 Selang in the academic year of 2014/2015.Keywords: MURDER Models, Image Media, Science Abstrak: Penggunaan Model MURDER dengan Media Gambar dalam Peningkatan Pembelajaran IPA Siswa Kelas IV SDN 1 Selang Tahun Ajaran 2014/2015. Tujuan penelitian ini adalah: untuk meningkatkan pembelajaran IPA menggunakan model MURDER dengan media gambar, mendeskripsikan langkah-langkah penggunaan model MURDER dengan media gambar, dan mendeskripsikan kendala dan solusi penggunaan model MURDER dengan media gambar. Penelitian Tindakan Kelas ini merupakan penelitian kolaboratif yang dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Subyek pada penelitian ini berjumlah 23 siswa. Simpulan penelitian ini adalah penggunaan model MURDER dengan media gambar dapat meningkatkan pembelajaran IPA siswa kelas IV SDN 1 Selang tahun ajaran 2014/2015.Kata Kunci : Model MURDER, Media Gambar, IPA